2001
DOI: 10.1046/j.1365-2761.2001.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and structure of lesions in the gills of Atlantic salmon, Salmo salar L., affected with amoebic gill disease

Abstract: Gills of Atlantic salmon, Salmo salar L., with amoebic gill disease (AGD), were analysed by routine histology to identify lesion morphology and distribution patterns. Numbers of lesions occurring dorsally, medially and ventrally in the gill ®laments were recorded as was lesion size, proximity to the gill arch and the degree of pathological severity involved. The mean number of lesions and pathological severity in the dorsal region of the second left gill arch were signi®cantly higher than that found ventrally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 12 publications
7
82
2
Order By: Relevance
“…Although fish in this study showed up to 90% AGDaffected filaments, the corresponding respiratory results do not reflect major acid -base disturbance. Experimental infections of AGD are typically far more aggressive compared to wild infections due to the increased pathogen loading that fish in culture conditions would not normally experience (Adams & Nowak 2001). Although the precise cause of AGD-associated mortality remains unknown, this, along with the results from the present study, suggests that AGDassociated mortality in cultured fish is not caused by respiratory failure.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Although fish in this study showed up to 90% AGDaffected filaments, the corresponding respiratory results do not reflect major acid -base disturbance. Experimental infections of AGD are typically far more aggressive compared to wild infections due to the increased pathogen loading that fish in culture conditions would not normally experience (Adams & Nowak 2001). Although the precise cause of AGD-associated mortality remains unknown, this, along with the results from the present study, suggests that AGDassociated mortality in cultured fish is not caused by respiratory failure.…”
Section: Discussionsupporting
confidence: 48%
“…These patches are present histologically as multifocal hyperplastic lesions, generally resulting in the fusion of secondary lamellae (Munday et al 1993, Adams & Nowak 2001. AGD-associated mortality has been presumed to be associated with a respiratory distur-bance, as both lethargy and respiratory distress have been described from salmonid AGD infections (Kent et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…correlated with a reduced proteolytic profile of the attenuated amoebae (Verissimo et al, 2013). The in vitro CPE identified here and its relevance to AGD is unclear given that extensive histological studies on AGD-affected salmon revealed no evidence of cytolytic activity (Adams and Nowak, 2001). While potential damage to host tissues may be masked by the exuberant proliferative host response it seems likely that the CPE demonstrated in vitro is evidence of an ECP with a less direct virulence mechanism.…”
mentioning
confidence: 75%
“…The causative agent of AGD is Neoparamoeba perurans as shown by molecular evidence (Young et al, 2007) and fulfillment of Koch's postulates (Crosbie et al, 2012). AGD is initiated by the association, and presumably attachment, of N. perurans to the gill epithelia (Lovy et al, 2007) which results in extensive gill epithelial hyperplasia and proliferation of amoebae associated with the hyperplastic lesions (Adams and Nowak, 2001). As N. perurans is a free-living amoeba and an opportunistic pathogen, AGD can be transmitted horizontally when N. perurans-containing mucus is sloughed off infected gills into the water column and the amoebae are free to colonise the gills of fish .…”
mentioning
confidence: 99%
“…All sections were viewed by a light microscope (Olympus) at 4-1000 × and fish with typical AGD lesions characterised by a single or multifocal epithelial hyperplasia of the gill lamellae, focal fusion of secondary lamellae and round to ovate interlamellar vesicles containing amoeba were considered AGD positive. Quantitative analysis of disease severity was conducted by estimating the number and size of AGD lesion on each filament (Adams & Nowak 2001). The percentage of lesioned filaments was determined by estimating the ratio of filaments with typical AGD lesions to filaments with no AGD lesions.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%